Impaired Binaural Hearing in Adults: A Selected Review of the Literature - Gallun, Frederick J. (Frontiers in Neuroscience, 2021)
Despite over 100 years of study, there are still many fundamental questions about binaural hearing that remain unanswered, including how impairments of binaural function are related to the mechanisms of binaural hearing. This review focuses on a number of studies that are fundamental to understanding what is known about the effects of peripheral hearing loss, aging, traumatic brain injury, strokes, brain tumors, and multiple sclerosis (MS) on binaural function. The literature reviewed makes clear that while each of these conditions has the potential to impair the binaural system, the specific abilities of a given patient cannot be known without performing multiple behavioral and/or neurophysiological measurements of binaural sensitivity. Future work in this area has the potential to bring awareness of binaural dysfunction to patients and clinicians as well as a deeper understanding of the mechanisms of binaural hearing, but it will require the integration of clinical research with animal and computational modeling approaches.